2018
DOI: 10.1093/rheumatology/key288
|View full text |Cite|
|
Sign up to set email alerts
|

A novel glucocorticoid-free maintenance regimen for anti-neutrophil cytoplasm antibody–associated vasculitis

Abstract: Early GC withdrawal in severe AAV is as effective for remission induction as the standard of care and is associated with reduced GC-related adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 34 publications
(11 reference statements)
5
42
0
2
Order By: Relevance
“…A recent study reported outcomes in 49 patients treated with a glucocorticoid-sparing regime. Here, the investigators used a cumulative dose of <0.7 g within the first three months [ 28 ]. However, and in contrast to our cohort, patients in this study and in PEXIVAS were routinely treated with intravenous methylprednisolone (up to 3 g) at disease presentation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported outcomes in 49 patients treated with a glucocorticoid-sparing regime. Here, the investigators used a cumulative dose of <0.7 g within the first three months [ 28 ]. However, and in contrast to our cohort, patients in this study and in PEXIVAS were routinely treated with intravenous methylprednisolone (up to 3 g) at disease presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Today, high dose glucocorticoids plus either rituximab or cyclophosphamide are used more often. Case series using combination rituximab and cyclophosphamide to spare glucocorticoid exposure have been published, but the evidence base supporting this practice remains weak 9697. The main limitation to use of rituximab is its cost,98 although biosimilar rituximab may cost less 99.…”
Section: Induction Of Remissionmentioning
confidence: 99%
“…The optimal dose and duration of glucocorticoid treatment remains an area of active investigation in both induction and maintenance of remission 125167168169170. For example, a single center study of 49 patients found that the combination of rituximab and cyclophosphamide with two weeks or less of glucocorticoids led to 96% of patients achieving remission at six months 125…”
Section: Emerging Treatmentsmentioning
confidence: 99%
“…One such combination approach using low-dose intravenous cyclophosphamide and rituximab, along with a rapid oral glucocorticoid taper, has been described in an open-label cohort study. Rates of remission at 6 months, mortality, long-term relapse rates, and renal outcomes were favorable when compared to those in matched historical controls from European Vasculitis Study Group studies (74,75). A similar approach, using a short course of oral cyclophosphamide and rituximab, has been reported in a single-center, retrospective case series of 129 patients, again showing favorable rates of remission induction and relapse (76).…”
Section: Combination Drug Therapymentioning
confidence: 56%